Electromagnetics for high-speed analog and digital communication circuits - Niknejad, Ali M., 1972- (Cambridge University Press, 2007)
Describes the fundamental electromagnetics of passive and active circuit elements, highlighting the various effects and potential problems in circuit design.
Keywords: Electronic circuits.; Electromagnetic compatibility.; Digital integrated circuits.; Linear integrated circuits.; Electromagnetism.; elektronické knihy; electronic books